Peningkatan Kualitas Hidup Anak Thalasemia Pada Masa Pandemi Covid-19 - Retno Puji Hastuti; Rina Mariani; Sri Ujiani3; Dewi Sri Sumardilah; Elizar Elizar (Universitas Muhammadiyah Yogyakarta, 2023)
Thalassemia is a disorder of hemoglobin synthesis with clinical manifestations of severe anemia. With a total of 35 sufferers in North Lampung, thalassemia causes complex health problems, especially during the Covid-19 Pandemic, including 1. The limited blood supply for transfusions due to decreased donors; 2. The problem of malnutrition leading to reduced immunity; 3. Psychological and school problems; 4. Not all thalassemia children in North Lampung had Hb-analysis as a diagnostic procedure; and 5. Low consumption of iron chelation drugs to prevent hemosiderosis. The community service aims to improve the quality of life for thalassemia children in North Lampung during the Covid-19 Pandemic. The Community service activities used a process approach (preparation, implementation, evaluation) involving several professions and related stakeholders (interprofessional collaboration). The target of the activities was thalassemia children and families who are members of the Association of Parents with Thalassemia (POPTI) North Lampung, with a total of 35 people. Data were analyzed with proportional descriptive analysis. The community service activities were 1. Formation of a Thalassemia Care Community consisting of 75 permanent blood donor volunteers; 2. Health education about the nutritional needs of thalassemia children and provision of nutrition packages to 33 people (94.28%); 3. Counseling on psychosocial problems and learning disorders in schools; 4. Facilitating story books in the treatment room of HM Mayjend Ryacudu Hospital; 5. Laboratory examination of Hb analysis and ferritin levels and socialization of the management of iron chelation treatment to 23 people (65.71%) of thalassemia children and their families. All activities were carried out with health protocols during the Covid-19 Pandemic. Suggestion: It is necessary to develop a network and increase the membership of the Thalassemia Care Community to six permanent donors for one thalassemia child. The Originality/Value/ Implication of this community service activity is the formatting of the North Lampung Thalassemia Care Network and Community.